2023
DOI: 10.1136/bmjopen-2022-065625
|View full text |Cite
|
Sign up to set email alerts
|

Clinical–functional characteristics and risk of exacerbation and mortality among more symptomatic patients with chronic obstructive pulmonary disease: a retrospective cohort study

Abstract: ObjectivesThe Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 classified chronic obstructive pulmonary disease (COPD) patients into more and less symptomatic groups. This study aimed to analyze the clinical characteristics, risk of future exacerbation and mortality among patients in more symptomatic group.DesignA retrospective cohort study.SettingData were obtained from patients enrolled in a database setup by Second Xiangya Hospital of Central South University.Participants1729 stable COPD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This finding is consistent with previous studies that reported nearly 65% of the included non-frequent exacerbation patients. 12 , 16 In addition, the majority of the patients had a low education level. In fact, China is a developing country and the overall level of education is not high in early time.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies that reported nearly 65% of the included non-frequent exacerbation patients. 12 , 16 In addition, the majority of the patients had a low education level. In fact, China is a developing country and the overall level of education is not high in early time.…”
Section: Discussionmentioning
confidence: 99%